Keuangan Perusahaan Multinasional Yang Terdaftar Pada Bursa Efek Indonesia - Ryan Febrianto; Hendra Ibrahim (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to conduct an in-depth analysis of foreign exchange risk management in the financial management of multinational corporations (MNCs). Currency exchange rate fluctuations between the countries in which MNCs operate can have a significant impact on the company's finances. The method used in this research is a qualitative approach using a literature review. Data was collected through a comprehensive search of relevant sources such as academic journals, books, and research reports. The results of this study reveal that foreign exchange risks are influenced by factors such as exchange rate fluctuations, political and economic stability, as well as microeconomic factors. MNCs employ various tools and techniques for foreign exchange risk management, including forward contracts, foreign exchange options, and foreign exchange hedging.